Factors Affecting Job Stress Among Employees in Bin Chen Parts Private Limited Company - Teoh, Kok Ban; Cordova, Miguel; Ng, Yi Hong; Lee, Gim Seng; Choy, Jin Feng; Kee, Daisy Mui Hung; Ng, Ruen Chye; Ang, Delon Wern Jian; Low, Song Han; Wan, Yong Hong; R G, Sushma; Warrier, Uma (Asia Pacific Journal of Management and Education (APJME), 2021)
There is a high level of stress faced by employees of Bin Chen Parts Private Limited Company. The research was conducted to examine the factors causing job stress in workplace. There are 36 respondents from Bin Chen Parts Private Limited Company collected in the present research by using quantitative measurements. Google form was selected to use in this research. The collected data from the research were adopted to verify the hypotheses of the research. The results show that there is a significant positive relationship between job demands and job stress. Conversely, the relationship between job resources and job stress is relatively negative. The results of the research will be finalized precisely and sent to Bin Chen Parts Private Limited Company to enhance the work-life in the company. The employers of the company are able to aware of the factors affecting job stress among employees in their company.